2018
DOI: 10.2174/1874256401810010016
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antibacterial Activity of Bergamot Peel Oil from Supercritical CO2 and Compressed Propane Extraction

Abstract: Objective: Essential oils are widely used as flavors and fragrances in the food, cosmetic and pharmaceutical industries, especially the bergamot peel oil due to the high polyphenols content, compared to other citrus species. Two types of polyphenols present in bergamot peel oil, brutieridin and melitidin, are directly related to cholesterol biosynthesis inhibition in a similar way as the statins. In this context, this work reports the extraction yields of bergamot peel oil obtained by super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…It is also important to note that SCCO 2 extraction favors a solvent-free product since CO 2 is removed during the depressurizing process, generating no residues, being a clean and alternative method [34]. e operating conditions of the extraction performed by Capelleto et al [18] (250 bar, density of 0.879 kg/m 3 ) give the fluid a solvating power similar to a conventional solvent like hexane, allowing the extraction of nonpolar chemical compounds such as terpenes [35]. e extraction yield using supercritical CO 2 was 8.02 ± 0.05 wt%, and the major Evidence-Based Complementary and Alternative Medicine components of C. xanthocarpa extract obtained by SCCO 2 were β-caryophyllene (11.67%), followed by c-cadinene (9.58%), α-cadinol (7.17%), viridiflorol (6.70%), and δ-gurjunene (6.48%), as previously reported by Capelleto et al [18].…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to note that SCCO 2 extraction favors a solvent-free product since CO 2 is removed during the depressurizing process, generating no residues, being a clean and alternative method [34]. e operating conditions of the extraction performed by Capelleto et al [18] (250 bar, density of 0.879 kg/m 3 ) give the fluid a solvating power similar to a conventional solvent like hexane, allowing the extraction of nonpolar chemical compounds such as terpenes [35]. e extraction yield using supercritical CO 2 was 8.02 ± 0.05 wt%, and the major Evidence-Based Complementary and Alternative Medicine components of C. xanthocarpa extract obtained by SCCO 2 were β-caryophyllene (11.67%), followed by c-cadinene (9.58%), α-cadinol (7.17%), viridiflorol (6.70%), and δ-gurjunene (6.48%), as previously reported by Capelleto et al [18].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have focused on the antibacterial potential of bergamot essential oil (BEO). In a recent study, the group of Kokina et al highlighted the effect of BEO against Staphylococcus aureus ATCC 25923 and S. Typhimurium ATCC 14028 [ 28 ], while Lazarotto et al and Nashad et al reported the inhibitory effect of BEO against Pseudomonas aeruginosa, Escherichia coli, Staphylococcus epidermidis and Streptococcus pyogenes [ 29 , 30 ]. Not least, the antifungal activity of BEO against clinically relevant Candida species was reported by Romano et al [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…В последнее время, однако, в пищевой, кормовой, фармацевтической и иных отраслях промышленности всё большее применение вместо «эфирных масел» находят экстракты, получаемые из аналогичного растительного сырья, но с использованием, в качестве экстрагента, сжиженного углекислого газа (СО2РЭ), который затем за счёт изменения давления и температуры конечного продукта полностью удаляется из последнего SahenaaI et al, 2009;Ibadullaeva et al, 2015;Valle et al, 2016;Lazarotto et al, 2018;Vieitez et al, 2018;Coelho et al, 2018]. Так, например, ООО «Биоцевтика», (РФ, Московская обл., г. Дедовск, https://biozevtika.ru) к настоящему времени уже не только разработала, но и внедрила в производство с последующей достаточно широкой реализацией целую линейку йогуртов, майонезов, растительных и сливочных масел, пряных смесей (сухих, жиро-либо водорастворимых), соков, лимонадов и т.п.…”
unclassified